THREE-VALUED PREDICATE CALCULI WITH THE SYMBOL OF UNCERTAINTY - Bolibekian, H. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
The question of equivalence of three-valued predicate calculi with the symbol of uncertainty of symmetric constructive logic is considered. For one of the considered calculi the mix elimination theorem is proved.